2020
DOI: 10.3390/ijms21113959
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Receptor is Involved in Mitochondrial Dysfunction Induced by Extracellular Alpha Synuclein in Neuroblastoma SH-SY5Y Cells

Abstract: The purinergic P2X7 receptor (P2X7R) belongs to a family of trimeric ion channels that are gated by extracellular adenosine 5′-triphosphate (ATP). Several studies have pointed to a role of P2X7R-dependent signalling in Parkinson's disease (PD)-related neurodegeneration. The pathology of (PD) is characterized by the formation of insoluble alpha-synuclein (α-Syn) aggregates—Lewy bodies, but the mechanisms underlying α-Syn-induced dopaminergic cell death are still partially unclear. Our previous studies indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 139 publications
(188 reference statements)
1
18
0
Order By: Relevance
“…However, its mutation or overexpression disturbed the process, which was confirmed by the inhibition of insulin-like growth factor 1 (IGF-1)-induced Akt activation [81]. Reduced phosphorylation/activation of Akt kinase was also observed in ours' and others' studies in neuronal cells treated with exogenous ASN [31,82]. ASN was also shown to inhibit BDNF signaling, leading to DA cell death [83].…”
Section: Asn-protein Network and Its Role In Neurotoxicitysupporting
confidence: 53%
See 1 more Smart Citation
“…However, its mutation or overexpression disturbed the process, which was confirmed by the inhibition of insulin-like growth factor 1 (IGF-1)-induced Akt activation [81]. Reduced phosphorylation/activation of Akt kinase was also observed in ours' and others' studies in neuronal cells treated with exogenous ASN [31,82]. ASN was also shown to inhibit BDNF signaling, leading to DA cell death [83].…”
Section: Asn-protein Network and Its Role In Neurotoxicitysupporting
confidence: 53%
“…Sci. 2021, 22, x FOR PEER REVIEW 7 of 27 and others' studies in neuronal cells treated with exogenous ASN [31,82]. ASN was also shown to inhibit BDNF signaling, leading to DA cell death [83].…”
Section: Asn-protein Network and Its Role In Neurotoxicitymentioning
confidence: 99%
“…Apart from its direct association with mitochondria, α-Syn may also indirectly affect their function. It was previously demonstrated that monomeric species of α-Syn, that are internalized less efficiently than oligomers (Hoffmann et al, 2019 ), can preferentially bind to and activate neuronal purinergic P2X7 receptor (Wilkaniec et al, 2017 ), which leads to a decrease in mitochondria membrane potential as well as elevation of mitochondrial ROS production (Wilkaniec et al, 2020 ). Also, oligomeric species of α-Syn were shown to induce selective oxidation and nitrosylation of mitochondrial proteins, triggering mitochondrial swelling and neuronal cell death (Tapias et al, 2017 ; Ludtmann et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, α-synuclein induced P2X7R activation in SH-SY5Yderived dopaminergic neurons that modulated mitochondrial dysfunction, ATP release, recruitment of pannexin-1 and decreased ATP degradation, with consequent cell death (Wilkaniec et al, 2017, Wilkaniec et al, 2020.…”
Section: Parkinson's Diseasementioning
confidence: 99%